Vertebral osteomyelitis concurrent with emphysematous pyelonephritis and psoas abscess. Issue 12 (28th October 2020) - Tanaka, Kojiro; Yonezawa, Naoki; Takei, Tetsuhiro
Abstract: Vertebral osteomyelitis associated with concurrent emphysematous pyelonephritis and psoas abscess is rare. Coexistence of these entities is a potentially life‐threatening condition, necessitating aggressive intervention. Abstract : Vertebral osteomyelitis associated with concurrent emphysematous pyelonephritis and psoas abscess is rare. Coexistence of these entities is a potentially life‐threatening condition, necessitating aggressive intervention.